Decoding Entrepreneurial Intentions among University Students in the Digital Age: A Machine Learning Approach to Leadership and Attributes - Karmagatri, Mulyani; Jumri, Isma Addi; Samyono, Widodo; Syamil, Achmad (Journal The Winners, 2024)
Leadership and personal attributes have significant roles in leading a successful business organization. Meanwhile, a new perspective in leadership and entrepreneurship research is how the pattern of leadership and personal attributes contribute to entrepreneurial intention. To fill the gap and explore the pattern, the research examines the role of leadership and personal attributes in shaping entrepreneurial intention. The research employs a mixed-method approach, combining exploratory analysis and machine learning techniques. Data were collected from 127 entrepreneurial students in West Java, Indonesia. Moreover, data were collected using a web-based questionnaire consisting of 38 indicators that reflect the five variables (motivation, expectation, risk resistance, negative attitudes, and leadership). The collected data were proceeded using exploratory factor analysis to test the reliability of each indicator and analyzed using a decision tree model to identify critical factors influencing entrepreneurial intention. The research findings reveal that negative attitudes are crucial in determining entrepreneurial intention, followed by motivation and leadership. The research explains how these attributes interact to influence entrepreneurial decisions. The research gives insight into improving the effective development program that fosters the key attributes by reducing negative attitudes. The research also contributes to the broader field of leadership and entrepreneurship, offering an understanding of the role of personal attributes and leadership in driving entrepreneurial action.